2011
DOI: 10.1016/j.neuroimage.2011.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mindfulness-based stress reduction training on intrinsic brain connectivity

Abstract: The beneficial effects of mindful awareness and mindfulness meditation training on physical and psychological health are thought to be mediated in part through changes in underlying brain processes. Functional connectivity MRI (fcMRI) allows identification of functional networks in the brain. It has been used to examine state-dependent activity and is well-suited for studying states such as meditation. We applied fcMRI to determine if Mindfulness-Based Stress Reduction (MBSR) training is effective in altering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
227
2
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(268 citation statements)
references
References 60 publications
26
227
2
13
Order By: Relevance
“…This study found increases in gray matter of the left hippocampus, posterior cingulate cortex, the temporo-parietal junction, and the cerebellum in individuals participating in a Mindfulness-Based Stress Reduction (MBSR) program compared to controls [45]. A separate study of individuals who had completed a MBSR program also showed greater interconnectedness of brain regions including between sensory systems (auditory and visual), and connections that indicate increased attention, sensory processing, and sensory awareness [46].…”
Section: Mindfulness and The Brainmentioning
confidence: 84%
“…This study found increases in gray matter of the left hippocampus, posterior cingulate cortex, the temporo-parietal junction, and the cerebellum in individuals participating in a Mindfulness-Based Stress Reduction (MBSR) program compared to controls [45]. A separate study of individuals who had completed a MBSR program also showed greater interconnectedness of brain regions including between sensory systems (auditory and visual), and connections that indicate increased attention, sensory processing, and sensory awareness [46].…”
Section: Mindfulness and The Brainmentioning
confidence: 84%
“…Another study showed changes in posterior insular function and connectivity linked to interoception as a function of mindfulness training (Farb et al 2012). The posterior insula is a region of particular interest to the present research because of its implication in auditory and interoceptive processing by both structural and functional neuroimaging research (Bamiou, Musiek, & Luxon 2003;Remedios, Logothetis, & Kayser 2009;Flynn 1999) and due to the previously demonstrated effect of mindfulness training on the activation and functional connectivity of this region (Kilpatrick et al 2011;Farb et al 2012;Kirk, Gu, Harvey, Fonagy, & Montague 2014). Changes in cortical thickness of the posterior insula may lead to changes in auditory processing, and the posterior insula may interact with other regions implicated in auditory processing, such as the left middle/superior temporal gyrus (MTG/STG) and right ventrolateral prefrontal cortex (vlPFC) in a network involved in the detection of novel auditory information (Petrides & Pandya 2002;Plakke & Romanski 2014;Rauschecker & Scott 2009;Schönwiesner et al 2007;Buse & Roessner 2016;Kiehl, Laurens, Duty, Forster, & Liddle 2001).…”
mentioning
confidence: 80%
“…Not only experienced meditators but also individuals receiving brief mindfulness training show changes in the activation and functional connectivity of brain regions, particularly within default, executive, salience, and sensory networks (Brewer et al 2011;Wells et al 2013;Kilpatrick et al 2011;Farb, Segal, & Anderson 2012;Mooneyham et al 2016). Similarly, both meditation expertise and training are associated with structural changes in distributed brain regions, including the insula, sensory cortices, prefrontal cortex, and hippocampus (Fox et al 2014;Hölzel et al 2011;Lazar et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, scores on trait mindfulness questionnaires (e.g. MAAS; Brown and Ryan 2003) increase with mindfulness training (Chambers et al 2008;Kilpatrick et al 2011;Orzech et al 2009). …”
Section: Introductionmentioning
confidence: 99%